2020
DOI: 10.1101/2020.02.08.934661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diverse Arctic lake sediment microbiota shape methane emission temperature sensitivity

Abstract: 37Northern post-glacial lakes are a significant and increasing source of 38 atmospheric carbon (C), largely through ebullition (bubbling) of microbially-39 produced methane (CH 4 ) from the sediments 1 . Ebullitive CH 4 flux correlates 40 strongly with temperature, suggesting that solar radiation is the primary driver of 41 these CH 4 emissions 2 . However, here we show that the slope of the temperature-42 CH 4 flux relationship differs spatially, both within and among lakes. 43Hypothesizing that differences i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…However, the microbial communities inhabiting polar lake sediments are still poorly characterized, and what drives community composition is relatively unknown. Although over the past few years several studies taking place in the polar regions have used next-generation sequencing to characterize microbial communities (Stoeva et al, 2014 ; Emerson et al, 2015 ; Hauptmann et al, 2016 ; Schütte et al, 2016 ; Wang et al, 2016 ; Mohit et al, 2017 ; Thaler et al, 2017 ), data on sediment microbial communities in these environments is still sparse. The available data are also biased toward small lakes and thaw ponds, thus underrepresenting large arctic lakes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the microbial communities inhabiting polar lake sediments are still poorly characterized, and what drives community composition is relatively unknown. Although over the past few years several studies taking place in the polar regions have used next-generation sequencing to characterize microbial communities (Stoeva et al, 2014 ; Emerson et al, 2015 ; Hauptmann et al, 2016 ; Schütte et al, 2016 ; Wang et al, 2016 ; Mohit et al, 2017 ; Thaler et al, 2017 ), data on sediment microbial communities in these environments is still sparse. The available data are also biased toward small lakes and thaw ponds, thus underrepresenting large arctic lakes.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, a MAG recovered from subarctic lake sediment metagenomes in northern Sweden, referred to here as SAL16, was characterized taxonomically as a member of the archaeal order Methanomassiliicoccales (Emerson et al ., 2020). However, despite being 95% complete, the MAG lacked genetic evidence for methanogenesis, which was unusual, given that all previously identified Methanomassiliicoccales were thought to be methanogens (Borrel et al ., 2014; Söllinger et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work suggested that a MAG, referred to here as subarctic lake (SAL) 16 (SAL16), assembled from methanogenic sediments of a subarctic lake in northern Sweden, lacked methanogenesis genes, despite being assigned as a Methanomassiliicoccales based on the genomic information and RDP assignment of the assembled and binned 16S rRNA gene (Bin 16 in Emerson et al, 2020). To further investigate whether these missing genes were the result of incomplete genome binning or were likely to be a true lack of methanogenic capabilities, MAGs were identified that were closely related to SAL16 in the Genome Taxonomy Database (GDTB; https://gtdb.ecogenomic.org/ tree) release 86 archaeal tree, including those which were also in the Ca.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Our results showed that the methanogens in LXZ glacier foreland soils were dominated by Methanomassiliicoccales (49%) and Methanomicrobiales (24%), which are consistent with those recovered from the NamCo wetland ( Deng et al, 2019 ), Zoige wetland ( Zhang et al, 2008 ), and Qilian Mountain alpine permafrost soils ( Wang et al, 2020 ). Methanomassiliicoccales has been identified from a wide range of environments, such as tropical peat swamp forest soils ( Too et al, 2018 ), lake sediment ( Emerson et al, 2020 ), and alpine cave soils ( Jurado et al, 2020 ). Methanomassiliicoccales is phylogenetically distant from other methanogen orders, and belongs to a large evolutionary branch composed of many non-methanogenic archaea ( Borrel et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%